The Development of Socially Inclusive Libraries in Šiauliai Region Providing Services for Children and Youth with Special Needs - Kulikauskienė, Kristina (Jaunųjų mokslininkų darbai, 2020)
One of socially vulnerable groups in society, which often faces social exclusion problems, is children and youth with special needs. In Lithuania, children with special needs comprise about 12.5 percent from the total number of children and youth up to 18 years (Statistics Department of Lithuania, 2020). It is a significant part of society and a group of library stakeholders, which needs to have access to library services since the earliest possible participation in educational, social and cultural activities can promote the development of these children. For this reason, it is important to study how library services meet the needs of and to assess how they are prepared to provide services for this group. In order to do this, the aim of this paper was to analyze the possibilities of Šiauliai region libraries social inclusion in the area of services for children and youth with special needs. To achieve this goal scientific literature was analyzed and a structured interview with 25 respondents was carried out by e-mail in empirical research, Research data was analyzed using a categorization method. Scientific literature analysis allowed the author to identify the main areas of library activities and services for children and youth with special needs. Empirical research provided an opportunity to assess how Šiauliai region libraries services meet the needs of children and youth with special needs and to examine their possibilities to maximise libraries social inclusion. Empirical research showed that Šiauliai region libraries social inclusion regarding their services for children and youth with special needs is insufficient in the context of library management, environment adaptation, cooperation development, information on cultural events, on library service dissemination. Regarding library management, there is a need for more detailed research into the needs of this target group, which could help to assess the needs of children and their representatives. Regarding environment and service adaptation, Šiauliai region libraries social inclusion can be raised by improving their infrastructure, technological equipment, expanding the variety of information sources and access to cultural services. It is also important to intensify libraries cooperation with organizations that represent children and youth with special needs and to more actively disseminate information that focuses on this target group.
Keywords: socially inclusive library; children and youth with special needs